The women inclusion on rugby: perceptions of Brazilian national team players - Flavia Volta Cortes de Oliveira; Helena Altmann; Renato Francisco Rodrigues Marques (Universidade Estadual Paulista (UNESP), 2019)
Abstract Aims: Women participation in sport is historically permeated by manifestations of discrimination, especially in male preserve practices. This study aimed to investigate and describe the processes of entry and performance of women athletes in rugby, as well as socio-cultural components of this field in relation to gender differences from the perspective of Brazilian women national senior team players. Methods: Semi-structured interviews with five athletes were performed and data analyzed based on the Grounded Theory method. Results: It was found that there are social barriers for women practice in rugby. By the other hand, better opportunities for the development of an athletic career are more available than in the past. Besides that, it has been perceived that the women players need to constantly prove that they can play hard to legitimize their athletic skills among men players. Conclusions: Even if the women participation in rugby is in a changing process of acceptance, barriers still need to be broken for a full social legitimation of these players' practice.